Digital Literacy in Islamic Education: An Integrative Multidisciplinary Strategy to Counter Radicalism and Disinformation on Social Media - Muhammad Ainur Rohim; M. Yunus Abu Bakar; Ali Mas’ud (CV. Media Digital Publikasi Indonesia, 2026)
The rapid expansion of digital information has created a paradox within contemporary Islamic education. On one hand, social media serves as an effective medium for da'wah; on the other, it has become a channel for disseminating radical ideologies and religious disinformation that threaten the sustainability of religious moderation in Indonesia. This study aims to describe an integrative multidisciplinary strategic model for countering radicalism and disinformation on social media. Employing a qualitative approach with a multiple case study design, data were collected through social media content analysis, in-depth interviews with Islamic education teachers, and participatory observations conducted in several pesantren across East Java. Thematic analysis was carried out with the assistance of qualitative data analysis software. The findings reveal five central components: the anatomy of digital radicalism and disinformation; the Framework of Islamic Learning and Technology for Ethical Reasoning; the integration of technological, narrative, and operational dimensions; the development and contextual validation of the FILTER prototype model; and the recontextualization of Islamic epistemology in the digital era. First, the vulnerability of young generations to radical content is shaped by weak critical thinking skills and fragmented religious understanding. Second, the integration of hadith studies, ushul fiqh, cognitive psychology, and digital communication proves effective in strengthening ideological resilience. Third, the FILTER model demonstrates its potential to enhance students’ ability to identify and reject problematic content during limited trials. Therefore, these findings affirm that multidisciplinary digital literacy strategies not only enhance learners’ technological competence but also reinforce ideological immunity against the growing waves of radicalism and disinformation. The implementation of the FILTER model further represents a new form of digital sanad an adaptive knowledge chain responsive to contemporary scholarly dynamics and technological developments.